The Impact of Financial Repression on the Economy of Bangladesh - Yousuf, Md. (Finance & Economics Review, 2024)
Purpose: The study’s objective is to examine the impact of financial repression on Bangladesh’s economy. Moreover, the impact of individual policy tools such as real deposit rate, interest rate restriction, capital account control, share of state-owned commercial bank in total advances, and statutory liquidity ratio will be investigated to find the specific policy that hampers economic activities. Method: The autoregressive distributed lag (ARDL) method, originated by Pesaran and Shin (1999) and expanded by Pesaran, Shin, and Smith (2001), will be used to look at the long-term relationship. The study uses time series data for Bangladesh’s economy from 1973 to 2022. Results: The findings of the ARDL approach confirm that repressive policies reduce economic growth over the sample period, and the effect becomes weaker after liberalizing the foreign exchange market. However, among the repressive policies, interest rate restrictions, statutory liquidity ratio, and the share of the state-owned bank in the commercial banks have significant adverse effects on economic growth. Implication: Policymakers should take proper measures to liberalize the financial sector to boost economic activity. The interest rate restrictions, which are already in effect and hamper the fair functioning of the loan market, should be withdrawn.